Extrapolation of the image of the motherhood of the bird in Al-Qama Al-Fahl's Diwan - Al-Qurashi, Amani Saud Khishan (Journal of Arabic Language Sciences and Literature, 2023)
Study Methodology: The study took into account the analytical descriptive approach, which is based on the inquisitive extrapolation of the image of the motherhood of the bird in the poetry of Al-Qamah Al-Fahal.The aim of the study: tracing the hair of the stallion's bite in order to reveal the image of the motherhood of the bird, and seeking to discover the poets' intentions from that.Results of the study: The study proved that: the image of the motherhood of the bird at the stallion’s bite denies the allegations and accusations that afflicted the pre-Islamic poetry, and denied the Arab mind creativity, and accused it of its superficiality, materialism, and lack of imagination, as it became evident that the pre-Islamic poet possessed a high sense that makes it go beyond the description of the appearance of things and beings To dive into her depths, and reveal her psychological feelings of fear, anxiety and tenderness in her highest form, which is the image of motherhood.The image of the motherhood of the bird was limited to ostriches alone. This is done by mentioning eggs and chicks together; The reason for this may be that the ostrich bird was close to the pre-Islamic poet in terms of its dwelling and its inability to fly.
Keywords: Motherhood; Birds; Arabic Poetry; Poet Al-Qamah Al-Fahal